Distinct gut microbiota composition among older adults with myocardial ageing - Wong, Jie Jun; Purbojati, Rikky; Tan, Ru San; Pettersson, Sven *; Koh, Angela S (Wiley Open Access, 2022)
Changes in cardiac structure and function occur with ageing and may lead towards ageing-related cardiovascular disease.1 Recent explorations into intestinal microbiota have provided important insights into shifts in microbial composition that occur in response to cardiovascular disease pathogenesis. Several proposed mechanisms include altered gut permeability, endotoxemia, and the systemic effect of metabolites including trimethylamine (TMA), short-chain fatty acids (SCFA), and secondary bile acids.1 However, causal associations between gut microbes and left ventricular (LV) function have yet to be proven. We sought to determine whether gut microbial composition is associated with left ventricular myocardial relaxation, an early manifestation of myocardial ageing, among older adults.